Democratizing global climate governance - Stevenson, Hayley, 1982-; Dryzek, John S., 1953- (Cambridge ; New York : Cambridge University Press, 2014)
"Climate change presents a large, complex and seemingly intractable set of problems that are unprecedented in their scope and severity. Given that climate change is both generated and experienced internationally, effective global governance is imperative for its resolution; yet, current modes of global governance have so far failed to provide effective responses. Hayley Stevenson and John Dryzek argue that legitimacy, accountability, deliberation and democracy are not just intrinsically important, but also increase the chances of successful collective action. Spanning topics of multilateral diplomacy, networked governance, representation, accountability, protest and participation, this book charts the failures and successes of global climate governance to offer fresh proposals for a deliberative system which would enable meaningful communication, inclusion of all affected interests, accountability and effectiveness in dealing with climate change; one of the most vexing issues of our time"--
Machine generated contents note: Preface; Acknowledgements; 1. The challenge of global climate governance; 2. Global climate governance as a deliberative system; 3. Governance with and without institutionalized authority: the importance of public space; 4. Authoritative global governance: the United Nations Framework Convention on Climate Change; 5. Emerging centers of networked authority; 6. Transmitting public concerns in the deliberative system; 7. Accountability; 8. Improving the global deliberative system; 9. Conclusion: looking for reflexivity.
Includes bibliographical references (p. 218-246) and index.
Keywords: Environmental policy -- International cooperation; Environmental protection -- International cooperation; Climatic changes -- Prevention -- International cooperation; Democracy and environmentalism; POLITICAL SCIENCE / History & Theory